2017
DOI: 10.12691/ajidm-5-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Distribution and Antibiotic Susceptibility Pattern of <i>group B Streptococcus β hemolytic </i>(GBS) in Vaginal Infections at Cotonou in Benin

Abstract: No orthodox practices disrupt the vaginal flora and expose it to pathogenic microorganisms including group B Streptococcus β hemolytic (GBS). The study aims to describe the bacterial profil and resistance of GBS to antibiotics. Retrospective study included 640 women at Cotonou suspected of vaginal infections or vaginal discharge during 1 st January 2004 to 31 st December 2015. Three swabs were collected and analyzed to identify the bacteria by standard biochemical reactions, diagnosis of bacterial vaginosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Primary studies conducted in the East African countries showed the colonization rates ranged from 3.0% to 28.8% [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; Central Africa,20.0% [27,28]; Western Africa, 2.5% to 34.2% [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]; Southern Africa, 1.77% to 48.23% [49][50][51][52][53][54][55][56][57]…”
Section: Introductionmentioning
confidence: 99%
“…Primary studies conducted in the East African countries showed the colonization rates ranged from 3.0% to 28.8% [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; Central Africa,20.0% [27,28]; Western Africa, 2.5% to 34.2% [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]; Southern Africa, 1.77% to 48.23% [49][50][51][52][53][54][55][56][57]…”
Section: Introductionmentioning
confidence: 99%
“…Genital carriage of S. agalactiae and E. coli has been studied in several countries because of the incidence of infection caused by these bacterial species and the carriage rate varies according to geographic area and region (Brochet et al, 2009;Gizachew et al, 2019;Lekala et al, 2015;Madrid et al, 2017). In Benin, Edmond et al (2017) Balaka et al (2005) also found similar results with an overall rate of 79.2% in mono-microbial and 20.8% in poly-microbial. Among the beta-lactams tested, ampicillin shows high resistance in almost all species.…”
Section: Discussionmentioning
confidence: 88%
“…The most sensitive molecule was gentamycin with 0% resistance to Gram positive bacteria except S. agalactiae (1/13 resistance). According to the study conducted in Benin on strains isolated from vaginal samples in women presenting symptoms, 66.7% of S. agalactiae were resistant to ampicillin, 61.5% resistant to gentamycin, 50.5% to erythromycin, and 91.7% with tetracycline (Edmond et al, 2017). Compared to the results obtained for the sensitivity of S. agalatiae to these antibiotics, the resistance rates reported by Edmond et al (2017) were globally higher.…”
Section: Genes Of Resistance To Mlsb P-value Ermb (%) Ermtr (%) Mef(a/e) (%)mentioning
confidence: 95%
See 1 more Smart Citation
“…Age also has an impact on the habitat of the vaginal microbiome [64]. As a result of the differences in microbial community composition among individuals, our understanding of the pathophysiology behind a wide range of illnesses, from atopic dermatitis to hepatocellular cancer, affecting certain areas of the body, is continually expanding [65,66]. It has been demonstrated that the VM's structure affects IVF results, particularly diagnostic conception rate, implantation rates, and live birth rates, all of which are pertinent in uterine transplantation, where the live birth of a healthy infant is the main objective.…”
Section: Influence On Sexual Health and Reproductive Healthmentioning
confidence: 99%